(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The paper examines the behaviour of SC (Schedule Caste) and ST (Schedule Tribe) expenditure in rural water supply sector in MP (Madhya Pradesh), covering the period from 2001-02 to 2017-18. Three types of examinations have been made in the study. The first is to find out trends of SC/ST expenditure in water supply and sanitation, water supply and rural water supply sector, and their percentage in total state expenditure. The second option is to look at per capita expenditure of SC/ST and the third is the utilization of the funds for SC/ST. Finding indicates that the quantum of expenditure on SC and ST in water supply and sanitation, water supply and rural water supply is much lesser than their population proportion. In MP, SC/ST constitutes about 43 percent of the rural population, while they are attracting only 34 percent of rural water supply budget. During last five years government has reduced the SC/ST expenditure in rural water supply and in 2017-18 government has stopped investing for them as the expenditure has reached at zero. Within the SC/ST, the ST as a social group have attracted very little expenditure as the expenditure made on them, government has discriminated against the STs in so far as the investments in water supply and sanitation and water supply is concerned. SC/ST per capita expenditure in water supply and sanitation, water supply and rural water supply is lower than state per capita expenditure. The analysis provides evidence that the variance of actual from the budgeted is more or less acceptable in state expenditure and social services expenditure, but it spills beyond permissible limits in the case of total rural water supply expenditure and SC/ST rural water supply expenditure. The under spending is in greater extent in the case of SC/ST, this vulnerable class is the greater victim of fund cutting, but whenever there is an overspending it goes to the other classes of society, the increased amount is not reflected in SCs and STs expenditure.